2011
DOI: 10.1093/ndt/gfr668
|View full text |Cite
|
Sign up to set email alerts
|

Changes in fibroblast growth factor 23 during treatment of secondary hyperparathyroidism with alfacalcidol or paricalcitol

Abstract: Alfacalcidol and paricalcitol increase the plasma levels of FGF23 equally and substantially in haemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 32 publications
3
35
0
2
Order By: Relevance
“…This would indicate that the differential effects of cinacalcet and vitamin D analogs on FGF-23 are not likely mediated by their effects on PTH but rather, may be mediated by direct effects on bone cells and/or other indirect effects on mineral metabolism, such as changes in Ca and/or P concentrations. Although previous studies have also noted these opposite effects of vitamin D analogs and cinacalcet on FGF-23 concentrations (16)(17)(18)(19)(20)(21)(22), this trial is unique in that participants were randomized to treatment with either cinacalcet or vitamin D analogs as monotherapy, thereby permitting a direct comparison of their effects. Both animal and human studies have shown that PTH administration increases FGF-23 (6-10), supporting the hypothesis that PTH is an important regulator of FGF-23.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would indicate that the differential effects of cinacalcet and vitamin D analogs on FGF-23 are not likely mediated by their effects on PTH but rather, may be mediated by direct effects on bone cells and/or other indirect effects on mineral metabolism, such as changes in Ca and/or P concentrations. Although previous studies have also noted these opposite effects of vitamin D analogs and cinacalcet on FGF-23 concentrations (16)(17)(18)(19)(20)(21)(22), this trial is unique in that participants were randomized to treatment with either cinacalcet or vitamin D analogs as monotherapy, thereby permitting a direct comparison of their effects. Both animal and human studies have shown that PTH administration increases FGF-23 (6-10), supporting the hypothesis that PTH is an important regulator of FGF-23.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that treatment of SHPT with vitamin D analogs is associated with increases in FGF-23 concentrations, whereas use of cinacalcet is associated with a reduction in FGF-23 (16)(17)(18)(19)(20)(21)(22). However, the majority of these trials were single-arm studies, and in those that used cinacalcet, it was added to standard-of-care treatment regimens that generally included vitamin D analogs.…”
Section: Introductionmentioning
confidence: 99%
“…FGF23 levels are increased as kidney function declines [47] and in dialysis patients treatment with vitamin D analogs increases FGF23 [20]. High FGF23 levels are associated with increased mortality and left ventricular hypertrophy in dialysis patients [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Further, VDRA administration in dialysis patients was shown to increase FGF23 concentrations [43], an established independent predictor of mortality in this population [44]. …”
Section: Another Paradigm Shift In Vdra Use For Shptmentioning
confidence: 99%